Improving Speaking Skills through Student Group Discussions at High School in Central Maluku - Nengsi Fatmawati Rifamole; Lidwina Sri Ardiasih; Dessy Yudha Santhi (Journal La Sociale, 2023)
Language is all about communication and the people they communicate with most are their friends and family. Language is a system for communicating with others using sounds, symbols, and words in conveying meanings, ideas, or propositions. This study is going to have qualitative research implementing a case study as the methodology of research. It aims to know about something in-depth, focusing on a single unit, such as one individual, one group, one organization, or one program. For more intensive research and better results. The number of respondents is 35 students. The instrument of the research is as follows observation checklist, questionnaire, test, and interview. the pupils were exposed to novel experiences, such as technology integration, which heightened their enthusiasm. Second, instructors' preparations from creating the learning process to presenting some answers to the issues experienced by previous group discussion implementers until the evaluation before the learning program began all contributed to the learning process's success. Third, after their projects were completed, the students' improvement in speaking abilities and other related skills may have been prompted by the input in English and topic materials they received from their teachers, as well as their learning from a variety of sources. Fourth, by their hands-on participation in completing the job, students gained many exposures to English through meaningful interactions with actual information. As a result, it may be concluded that group discussion is valuable for instructors to use in the classroom, particularly in EFL learners.